Pengetahuan Pemenuhan Gizi Pada Ibu Hamil Dalam Upaya Pencegahan Stunting Di Wilayah Kerja Puskesmas Batulicin - Suhartini, Sri; Iswandari , Novita Dewi; Kurniawati, Darini (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Good nutritional status is one of the determining factors for the success of health development which is an inseparable part of overall national development. Pregnant women need more nutrients than not pregnant. The purpose of the study was to determine the picture of knowledge of nutritional fulfillment in pregnant women towards stunting prevention in the Working Area of the Batulicin Health Center. Quantitative research with a cross sectional approach. There were 30 samples with accidental sampling technique. Univariate data analysis. The results of the study of respondents' characteristics based on the most age obtained the highest percentage results were at the age of not at risk (aged 20 to 35 years) as many as 25 respondents or 83.3% and at the high education level (high school to college) as many as 18 people (6%). The highest level of knowledge in the good category was 19 people or 63.3%, the other categories in the results were sufficient and lacking.